Association between primary dysmenorrhoea on quality of life, mental health and academic performance among medical students in Indonesia: a cross-sectional study - Reynardi Larope Sutanto; Herbert Situmorang; Kevin Tjoa; Rivaldo Rivaldo (BMJ Open)
Objectives To investigate the association between primary dysmenorrhoea and quality of life, mental health and academic performance among medical students in Indonesia.Design A cross-sectional study using an online survey was conducted among Indonesian medical students. Primary dysmenorrhoea occurrence and severity, as well as their associations with quality of life, mental health and academic performance, were assessed using validated questionnaires. The associations of dysmenorrhoea occurrence and severity were analysed alongside other potential independent variables, including age, region, stage of study and parental income. Statistical analyses included χ2 tests, t-tests and multiple regression models to adjust for confounders (p<0.05).Setting and participants Indonesia (June–July 2021: n=630 medical students).Outcomes The primary outcomes were quality of life, mental health and academic performance, assessed as dependent variables. Quality of life was measured using the Quality of Life Scale, mental health was assessed through depression and stress scores from the Depression Anxiety Stress Scales-42; and academic performance was evaluated through concentration and activity disruption, absenteeism and cum laude grade point average (GPA). The independent variables were primary dysmenorrhoea occurrence and severity, categorised as mild or moderate-to-severe using the Verbal Multidimensional Scoring System.Results Primary dysmenorrhoea was significantly associated with reduced quality of life, mental health challenges and academic disruptions. Students with dysmenorrhoea had significantly lower Quality of Life scores (–1.82, 95% CI: –2.63 to –1.02; p<0.001), with moderate-to-severe pain linked to an even more significant reduction (–2.09, 95% CI: –2.54 to –1.63; p<0.001). Dysmenorrhoea occurrence was significantly associated with depression (OR 2.16, 95% CI: 1.23 to 3.81; p=0.007), while severity was associated with both depression (OR 2.07, 95% CI: 1.47 to 2.92; p<0.001) and stress (OR 1.82, 95% CI: 1.26 to 2.62; p<0.001). Dysmenorrhoea occurrence and severity significantly disrupted concentration (OR 12.92, 95% CI: 6.14 to 27.22; p<0.001 and OR 7.24, 95% CI: 4.68 to 11.19; p<0.001, respectively), activities (OR 34.95, 95% CI: 4.77 to 256.16; p<0.001 and OR 6.92, 95% CI: 4.63 to 10.36; p<0.001) and absenteeism (OR 12.10, 95% CI: 1.65 to 88.83; p=0.014 and OR 5.65, 95% CI: 3.32 to 9.63; p<0.001). Cum laude GPA was not significantly associated.Conclusions Primary dysmenorrhoea is significantly associated with the quality of life, mental health and academic performance of medical students in Indonesia. Addressing its implications can enhance student well-being and academic outcomes.